Attitudes towards homosexuals in seven Caribbean countries: implications for an effective HIV response. Issue 12 (2nd December 2017) - Beck, Eduard J.; Espinosa, Kenika; Ash, Tanisha; Wickham, Peter; Barrow, Christine; Massiah, Ernest; Alli, Ben; Nunez, Cesar
ABSTRACT: Between 2000 and 2015, the number of people newly infected with HIV in the Caribbean decreased by 76% and HIV-related deaths by 42%. The number of people living with HIV (PLHIV) on anti-retroviral therapy (ART) increased from near zero to 50% (44% to 57%) in 2015. In many Caribbean countries communities of men-who-have-sex-with-other-men (MSM) have higher incidence and prevalence of HIV. They are often stigmatized and subjected to both social and institutional discrimination. This study compared attitudes of the general public obtained through public opinion polls 2013–2014 towards homosexuals and willingness to socialize with them in seven Caribbean countries. Informants were asked if they "hate, tolerate or accept" homosexuals and if they would socialize with them. In St. Vincent 53% indicated they "hate" homosexuals, compared with 12% in Suriname; the converse was observed for those who "accept" homosexuals; 63% of St. Vincent informants would not socialize with homosexuals, compared with 25% in Suriname. Findings for the other 5 countries fell within these ranges. Women were more likely to accept and socialize with homosexuals, as were informants with a tertiary education and "passive" religious believers. These groups are less likely to adhere to a culture of "compulsory heterosexuality" or "hyper-masculinity" dominant among Caribbean men. The homophobic views expressed by these cultures result in stigma and discrimination by members of the "general" public towards MSM. This negatively affects the involvement of MSM in successful national HIV responses. Public messaging, communications campaigns and educational measures need to be employed to change the culture of "compulsory heterosexuality" or "hyper-masculinity" that result in stigma and discrimination of homosexuals to improve early access to services by MSM. Repeat use of well performed opinion polls is one method that can be employed to monitor progress over time in "key" and "general" populations.